Experimental investigations on a process adapted material testing method for hydroforming of tubular components - Reblitz, Jonas; Merklein, Marion (SheMet2025, 2025)
In the automotive sector, an important strategy for reducing CO2 emissions is lightweight construction. In this regard, body-in-white parts offer a high potential for weight reduc-tions by substituting conventional steel parts with tubular, aluminum-based components. Due to their high strength-to-weight-ratio and high crashworthiness, tube profiles are often used as safety-relevant car body components. As lightweight design becomes increasingly important, complex part geometries are required, which can be realized by hydroforming. Especially for structural components, an exact determination of the material properties is necessary, in order to achieve a high prediction accuracy of FE-simulations. Thus, a failure-free component production has to be enabled. However, due to a varying stress and strain state, the tensile test according to DIN EN ISO 6892 as a standard characterization method is only insufficiently suitable for the characterization of tube profiles for a hydroforming process. For this purpose, a new testing method has been developed and investigated within this paper, which provides new insights regarding the material behavior of tubular components. The testing-rig is based on a bulge test, which reproduces the stress and strain state of a hydroforming process. By comparing the results of the material characterization with those of a tensile test, the differences in the mechanical properties depending on the testing method are evaluated. During the test, the surface strains and the internal pressure are varied and recorded. Based on these findings, a more accurate prediction of FE-simulations is aspired in future research wor
Keywords: Hydroforming; Aluminum; Tube Bulge Test